The Effectiveness of Improving the Economy of the Trirenggo Village Community through the Trirenggo Culinary Park - Alicia Maharani; Muhammad Eko Atmojo (Kemudi, 2025)
Abstract: Poverty is still a crucial issue in Bantul Regency, including in Trirenggo sub-district. This study aims to evaluate the effectiveness of local government and BUMKal initiatives in developing Trirenggo Culinary Park as an effort to improve the community's economy. Using descriptive qualitative methods, this study collected data through observation, interviews with traders and BUMKal managers, as well as secondary data analysis such as village economic growth data. This research examines the factors that contribute to the success of Taman Kuliner, including the utilization of local potential (Trirenggo Field), financial support and policies that support MSMEs, the active role of BUMKal in management, community participation, and promotion strategies through social media. The results show that Taman Kuliner has had a positive impact on the local economy, indicated by increased village economic growth and increased trader income. The study concludes that a community-based economic empowerment model, with government support and active community participation, is effective in improving welfare and reducing poverty levels.